Impact and Management of Loss of Eyebrows and Eyelashes - Michela Starace; Stephano Cedirian; Aurora M. Alessandrini; Francesca Bruni; Federico Quadrelli; Daniel F. Melo; Tatiana Silyuk; Andrei Doroshkevich; Bianca M. Piraccini; Matilde Iorizzo (Adis, Springer Healthcare, 2023)
Abstract Eyelashes and eyebrows have different functions, ranging from practical purposes such as protecting the eye apparatus from external hazards to the definition of our facial expression. For this reason, their loss could have both functional and psychological impact on patients' quality of life. Complete or partial loss can occur any time during life, and identifying the cause is mandatory to establish a correct and prompt treatment. The aim of this paper is to create a practical guide for the management of the most common causes of madarosis to the best of our knowledge.